Nonresonant tunneling in InGaP/InAlP asymmetric double quantum wells - Robinson, G. Y., author; Woods, M., author; Hafich, M. J., author; Rocca, Jorge J., author; Menoni, C. S., author; Chilla, J. L. A., author; Buccafusca, O., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1993)
Nonresonant tunneling rates have been measured in InGaP/InAlP asymmetric double quantum-well structures for which optical phonon assisted tunneling is energetically forbidden. For an initial photoexcited carrier density of 2.4 × 1011 cm-2, tunneling times of 220, 60, and less than 9 ps have been measured in samples with barrier thickness 4.5, 3.0, and 1.5 nm, respectively. The tunneling times were found to be strongly dependent on carrier density. The measured tunneling times and their dependence on carrier density are compatible with impurity scattering being the dominant mechanism assisting the tunneling.